Why Do CSR Governance Institutions Fail in Developing Countries: A Case Study of The Ghana Business Code - Brobbey, Kwaku A. (2013)
The effect of globalization in the last few decades spearheaded by the transnational operations of businesses has driven the exercise of societal regulation and control beyond state authority into a sphere of global governance. Corporate Social Responsibility (CSR) has been seen to hold the key to effective global governance through its institutions. As a concept with diverse characterization and practice across nations, CSR has become a global concept that development seeking and sustainability oriented businesses cannot overlook.